Rancang Bangun Sistem Informasi Surat Tugas Online dengan Metode Prototype di PT PLN (Persero) Sumatera Utara - Yanti Yanti; Eko Hariyanto; Rio Septian Hardinata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
PT PLN (Persero) Sumatera Utara is a company engaged in the electricity sector, specifically as a 20 kV distribution control implementing unit whose job is to maintain the reliability of the 20 kV system in the work area of North Sumatra which includes Medan to Nias Island. The wide reach of the work scope of PT PLN (Persero) Sumatera Utara causes employees to work outside their positions. One of the travel documents that must be carried by employees who carry out work assignments in the field is a letter of assignment. PT PLN (Persero) Sumatera Utara so far still uses a manual assignment letter making system. Based on the research that I did, there were a number of obstacles, especially when there was an emergency job because the supervisor who was authorized to sign the assignment letter was in a meeting, or on a day off, or was out of the office. It is very important that an assignment letter is carried by employees when working in the field, either as a travel document, or as the identity of an official official from the company so that it does not raise customer suspicion about the activities carried out by the PLN officer. To accelerate the process of approval of the assignment letter, an Online Assignment Letter Information System Design with the Prototype Method was made at PT PLN (Persero) Sumatera Utara. The design and build of this Online Assignment Letter Information System has several features, namely as an admin, as a driver, as a user and as approval. The Information System Design is expected to speed up the approval process for assignment letters for employee official travel at PT PLN (Persero) Sumatera Utara